2012
DOI: 10.17221/6464-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Mycoplasma bovis field isolates to antimicrobial agents

Abstract: ABSTRACT:The purpose of this study was to determine the antibacterial susceptibility of field isolates of Mycoplasma bovis originating from the upper respiratory tract of cattle of different ages. Bacteriological examination of 90 nasal swabs collected from calves at three months of age identified M. bovis in 31 (34.44%) samples. Seventeen (18.88%) of these animals still housed M. bovis in their nasal cavity at nine months and five animals (5.55%) still at seventeen months of age. M. bovis were confirmed by bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…High susceptibility of M. dispar isolates to tulathromycin makes it an attractive drug for treating mycoplasma infections in the field. Furthermore, in vivo investigations of tulathromycin have demonstrated a broad spectrum of efficiency in the therapy of bovine respiratory disease [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High susceptibility of M. dispar isolates to tulathromycin makes it an attractive drug for treating mycoplasma infections in the field. Furthermore, in vivo investigations of tulathromycin have demonstrated a broad spectrum of efficiency in the therapy of bovine respiratory disease [13].…”
Section: Resultsmentioning
confidence: 99%
“…DNA from isolated mycoplasma was extracted with 5 % solution of Chelex (Sigma, USA). Isolated microorganisms were analyzed by PCR using forward primer, MW28 (5'-CCAGACTCCTACGGGAGGCA -3') and reverse oligonucleotide primer MW29 (5'-T GCGAGCATACTACTCAGGC -3') (Grida Lab, Lithuania) that are specific for the Mollicutes class [13]. This pair of primer generates a 560 bp product.…”
Section: Methodsmentioning
confidence: 99%
“…Once these plates were cooled a bacterial lawn was prepared by spreading 100 μl from the above prepared bacterial suspension using sterile swabs. Wells of 6 mm in diameter were punched into the agar and filled with 100μl of the antimicrobial under investigation at a concentration of 1 μg/ml 13 . The plates were then incubated at 37 o C for 24 hours before zones of inhibition were measured using a caliper 14 .Each extract was analyzed in triplicate; the mean values are presented.…”
Section: Media Preparation and Antibacterial Activitymentioning
confidence: 99%
“…Infrequent or no resistance has been reported to enrofloxacin or florfenicol (Francoz et al, 2005, Gerchman et al, 2009, Hirose et al, 2003, Rosenbusch et al, 2005, Siugzdaite et al, 2012. Successful treatment of M. bovis pneumonia and arthritis in calves using valnemulin in the milk from four days of age for three weeks has also been reported (Stipkovits et al, 2001).…”
Section: Disease Prevention and Controlmentioning
confidence: 99%
“…In addition, in the past decade, in vitro susceptibility studies have shown an increased resistance to antimicrobials commonly used to treat infections associated with M. bovis; in particular oxytetracyclines, spectinomycin, tilmicosin and chlortetracycline (Francoz et al, 2005, Gerchman et al, 2009, Hirose et al, 2003, Rosenbusch et al, 2005, Siugzdaite et al, 2012. Infrequent or no resistance has been reported to enrofloxacin or florfenicol (Francoz et al, 2005, Gerchman et al, 2009, Hirose et al, 2003, Rosenbusch et al, 2005, Siugzdaite et al, 2012.…”
Section: Disease Prevention and Controlmentioning
confidence: 99%